2017
DOI: 10.1007/s11032-017-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for heat tolerance of reproductive traits in tomato (Solanum lycopersicum)

Abstract: Global warming has become a worldwide concern due to its adverse effects on agricultural output. In particular, long-term mildly high temperatures interfere with sexual reproduction and thus fruit and seed set. To uncover the genetic basis of observed variation in tolerance against heat, a bi-parental F2 mapping population from two contrasting cultivars, i.e. Nagcarlang and NCHS-1, was generated and phenotyped under continuous mild heat conditions for a number of traits underlying reproductive success, i.e. po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 43 publications
12
63
1
Order By: Relevance
“…Therefore, this is the first time that a QTL related to this trait was described. The QTL sl8 did not colocalize with any previous identified QTLs [78,79], suggesting that a new stable locus controlling stigma length was detected.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, this is the first time that a QTL related to this trait was described. The QTL sl8 did not colocalize with any previous identified QTLs [78,79], suggesting that a new stable locus controlling stigma length was detected.…”
Section: Discussionmentioning
confidence: 75%
“…Whether there is a physiological basis for these correlations or whether the traits each have a unique, but genetically linked basis remains to be investigated. Analysis of the genetic architecture behind important sub-traits may be pursuit using crosses between specific contrasting cultivars, such as Nagcarlang and NCHS-1 in case of pollen thermotolerance (Xu et al 2017). The suitability of Nagcarlang for such a study is supported by the finding that it was among the best performing genotypes regarding pollen fertility and fruit set under high temperature field conditions and general combining ability of these traits (Dane et al 1991;Bhattarai et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is a complex trait, and higher heritability may be found by separating the underlying individual key traits affecting fruit set. Indeed, we have recently reported two major QTLs for PN and PV in an S. lycopersicum mapping population (Xu et al 2017a). In the current study, screening of clones of individuals for PN and PV under LTMH in climate chambers indicated that a large fraction of the total phenotypic variance was explained by the genetic variance.…”
Section: Discussionmentioning
confidence: 98%